Multilayered Phantom for Input Impedance Evaluation of Human Body Communication Electrodes - Dairoku Muramatsu; Fukuro Koshiji; Kohji Koshiji; Ken Sasaki (EAI Endorsed Transactions on Cognitive Communications, 2016)
This paper presents the input impedance measurement of a human body communication electrode by using newly developed multilayered phantom. Based on the comparison between analysis and measurement values, it was found that the multilayered phantom can be used for accurate evaluation.